Systematic Literature Review - Turning Heads: Quantifying Hedonic, Eudaimonic, and Behavioural Engagement in 360° Tours - Rizal, Chairul; Saari, Erni Marlina Binti (Indonesian Scientific Journal, 2026)
This systematic literature review (SLR) examines the relationship between 360° virtual experiences, user engagement, and conversion outcomes. It explores how immersion influences emotional, cognitive, and behavioral responses across fields such as education, tourism, cultural heritage, retail, and gaming. Drawing from empirical studies published between 2013 and 2025, the review investigates how factors like presence, perceived control, enjoyment, and cognitive load mediate engagement in immersive environments. Experimental and quasi-experimental designs dominate the analyzed studies, often using frameworks such as PLS-SEM to assess mediation and moderation effects. Findings show that interactivity (hotspots, mini-maps, gamification) and guidance mechanisms (narration, AI support) tend to enhance behavioral engagement, while high visual fidelity, contextual relevance, and user-centered control strengthen both hedonic and utilitarian conversions, including purchase intentions and revisit likelihood. However, gaps remain in methodological rigor, including small samples and inconsistent engagement metrics. The review concludes that effective 360° virtual experiences integrate emotional engagement with usability to transform immersion into measurable outcomes. It recommends future research to emphasize cross-domain comparisons, standardized measures, and longitudinal studies to better understand how immersive systems sustain engagement and influence conversion behavior over time.